1973
DOI: 10.1090/s0002-9939-1973-0385860-9
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Steenrod-Hopf invariants for stable homotopy theory

Abstract: Abstract.In his paper On the groups J(X). IV, Adams suggested that one might try to continue his d and e invariants to a sequence of higher homotopy invariants, each defined upon the vanishing of its predecessors and each taking its value in a certain Ext group. Recently he pointed out the efficacy of relocating his d and e invariants in Ext groups formed over a certain abelian category of comodules. It is the purpose of this note to carry out the program suggested above in a setting of the sort just mentioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

1976
1976
1977
1977

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(1 reference statement)
1
2
0
Order By: Relevance
“…We also note that this lemma corrects Proposition 5 of[3] from which Propositions 1 and 2 now follow except the minus signs in their statements disappear.) PROOF OF LEMMA.…”
supporting
confidence: 56%
“…We also note that this lemma corrects Proposition 5 of[3] from which Propositions 1 and 2 now follow except the minus signs in their statements disappear.) PROOF OF LEMMA.…”
supporting
confidence: 56%
“…More precisely in case q + 1 = 2k, if (M2q, F) is a framed manifold whose Thorn invariant is/ E irlq(S°), then Browder showed that the Kervaire invariant, K(M2q, F), is one if and only if/projects to h\ in £¿'2*+'(5°). On the other hand, the present author [3] introduced homotopy invariants Ix and 72 which are defined on certain subgroups of the homotopy groups trJ(X) of a spectrum X and which take their values in the E2 term of an Adams spectral sequence for X. For the mod 2 Adams spectral sequence of S° and an element/ E ir2q(S°), I2(f) is always defined, and if q + 1 = 2k, A2 survives if and only if there is/ G w2*+<_2(S°) so that 72(/) = A2.…”
mentioning
confidence: 54%
“…Occasionally we shall regard £ as a functor on the stable category and denote induced maps on Ex by a subscript "*" and induced maps on (sub) quotients of £, by a subscript "*" (which convention is consistent with the above usage of sharped morphism letters for induced homomorphisms on Ext). In [3], it was shown that Proof. Let x(q + 1) G H2q+x(C(d)) be the element in the basis dual to the basis {Sq*x} for //2?+I(C(w)) corresponding to Sq9+1x, where x G //?…”
mentioning
confidence: 99%